In the eternal shade - Johnson, Bryan C., author; Becker, Leslee, advisor; Levy, E. J., committee member; Alexander, Ruth, committee member (Colorado State University. Libraries, 2015)
This is a novella concerning modern disillusionment, gender roles, and interpersonal relationships. Leon, Cheryl, and Alex are a family that lives outside of a small Indiana town, near a small stand of trees. Leon is working on a graphic novel based on the journal of great-great-great-grandfather, Cheryl is a trained veterinarian who is working at a job below her qualifications, and Alex is an eight-year-old girl with an imagination that is just starting to butt up against the real world.

A fox with mange takes up residence in the shed where Leon does most of his work; Cheryl decides to try and treat it from the shack, while Leon resents the intrusion into his work space and Alex thinks it's some sort of monster (influenced by the fantasy stories Leon writes for her). Eventually, Leon gets frustrated with his lack of progress and tries to work in Alex's tree fort, where he climbs to the top of the tree and eventually falls. When Alex tries to alert Cheryl to this and save Leon, Cheryl thinks Alex is just telling yet another of her stories. Alex, thinking the fox is behind all of this, murders the fox in the shed.